Ideological motives and taxation by armed groups. (May 2022) - Breslawski, Jori; Tucker, Colin
Which armed groups are the most likely to tax civilians? A common assumption is that armed groups only tax civilians when they lack access to other sources of revenue. However, recent insights have pointed to the fact that economic considerations are not the only influence on groups' decisions to tax civilian populations. In this article, we argue that armed groups with a communist ideology are more likely to tax civilians than other groups because it serves as a testament to their ideological goals. We conduct a statistical analysis of armed groups operating from 1990 to 2015 and find support for our argument.